Cluster Preface: Metathesis Reactions beyond Olefins - Morandi, Bill (Synlett, 2019)
studied at the ETH Zurich from 2003–2012, earning a B.Sc. in biology, an M.Sc. in chemical biology and a Ph.D. in organic chemistry working with Prof. Erick M. Carreira. After a postdoc with Prof. Robert H. Grubbs at CalTech, he led an independent Max Planck Research Group from 2014–2018 at the Max-Planck-Institut für Kohlenforschung, Germany. Since July 2018, he is a tenured Associate Professor at the ETH Zurich where he holds a chair in synthetic organic chemistry. His independent research program targets the development of new concepts in catalysis, with a particular emphasis on employing inexpensive and sustainable catalysts to transform broadly available feedstocks, such as polyols and hydrocarbons, into valuable building blocks for applications in medicine and materials science.